Evaluation and Optimization of Bypassed Oil in Carbonate Reservoir at Mature Field with Integration of Saturation Log and Cement Bond Quality - Agus Amperianto; Dyah Rini Ratnaningsih; Dedy Kristanto (Journal of Petroleum and Geothermal Technology, 2021)
AA field is a unitized asset operated by Corporate Oil Company since May 2018. The main producing formation of AA field is a reef build-up carbonate reservoir. The field has been on production since 2004 with OOIP of 297 MMSTB. As of November 2019 the cumulative production was estimated 120.7 MMSTB with RF of 41%. The carbonate reservoir has properties with relatively high heterogeneity –both vertically as well as laterally – which leads to production variation of the wells. The production performance shows an estimated 30% decline and significantly increasing water-cut. The production data shows a much faster water production compared with the cumulative production, which is also the greatest challenge in the AA field.There are several key contributing factors for the water production in AA field:Water channeling behind casing due to poor cement bond. This is supported by Chan Plot analysis.Uneven production of the wells leading to varying water rise and introduces difficulty in water contact determination.Water coning due to production exceeding the critical rate.Several efforts have been performed to optimize production, namely: identification of the potential of remaining hydrocarbon (bypassed oil) in the wells by evaluating current saturation evaluation through downhole surveillance, estimation of current water contact and cement bond improvement.The preparation steps of the production optimization process are summarized below:Screening of Candidate WellsEvaluation of Cement Bond QualityWellsite Execution for Bypassed Oil EvaluationWell PreparationOptimum C/O Log to Evaluate Current Saturation and to Identify Bypassed Oil ZonesBypassed Oil Interval ProductionThis section discusses one of successful cases in the production optimization effort implemented in the AA- field.AA-12 wellThe last production of AA-12 well was 84 BOPD. Chan plot showed possibility of water channeling, which was supported by CBL result. The zone of existing perforation interval was indicated to have “free pipe” behind the casing. Remedial cementing was then performed until sufficient zonal isolation was obtained. After subsequent CBL confirmed good zonal isolation, C/O log was then performed. The C/O log result indicated several reservoir zones with potential bypassed oil. The new production interval was selected based on following consideration: So between 55-60%, height above current OWC of 185 ft (56 m), distance to the adjacent wells of 1306 ft (398 m), porosity 12-17% and Production test of the new perforation resulted in 2186 BOPD with 0% water-cut.